2015
DOI: 10.1016/j.csr.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Depositional variability of estuarine intertidal sediments and implications for metal distribution: An example from Moreton Bay (Australia)

Abstract: This study examines the patterns of depositional variability, sediment geochemistry and metal distribution in intertidal areas of Moreton Bay, southeast Queensland, Australia. Recent concern over increasing human impact on the bay has generated the need to obtain evidence on how the disturbance of the depositional setting might affect the natural estuarine environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…High concentrations of metals in sediments can potentially have toxic effects on resident aquatic ecosystem and can make fish, crustaceans, and bivalves unsuitable for human consumption [42]. Coates-Marnane et al [12] reported trace metal (lead, zinc and copper) deposits in sediment core samples collected in the Moreton Bay region. Heavy metals, albeit below trigger values, were found in our previous studies at all sites sampled in this region [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High concentrations of metals in sediments can potentially have toxic effects on resident aquatic ecosystem and can make fish, crustaceans, and bivalves unsuitable for human consumption [42]. Coates-Marnane et al [12] reported trace metal (lead, zinc and copper) deposits in sediment core samples collected in the Moreton Bay region. Heavy metals, albeit below trigger values, were found in our previous studies at all sites sampled in this region [8].…”
Section: Discussionmentioning
confidence: 99%
“…Depths of active bioturbation are unknown, but analysis of geochemical tracers in mud cores by Coates-Marnane et al [13] indicate recent mixing of sediments to depths >40 cm. Morelli and Gasparon [12] found less mixing in cores from shallow and intertidal environments in Moreton Bay; cores near seagrass-dominated regions showed the lowest disturbance, with mixing confined to the top 10 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreton Bay is one of the largest estuarine systems in Australia, its waters extend from Caloundra to the southern tip of South Stradbroke Island, and this region is associated with diverse biota and ecosystem complexity. For instance, extensive seagrass beds provide important feeding habitats for turtles and dugongs, and mangrove forests offer critical nursery habitats for juvenile fish (Dennison and Abal 1999;Morelli and Gasparon 2015). Intertidal sand and mudflats are expansive along the coastline of this region (e.g.…”
Section: Characterising Marine Bioregions and Associated Biodiversitymentioning
confidence: 99%